Low-cost synthesis of heterocyclic spiro-type hole transporting materials for perovskite solar cell applications. (17th April 2018) - Govindan, Venkatesan; Yang, Kai-Cheng; Fu, Yung-Sheng; Wu, Chun-Guey
Abstract : The new spirobased PSC used HTM SFX-TPAM with good photovoltaic performance was prepared through low cost facile route. Abstract : Four heterocyclic spiro-type hole transporting materials (HTMs) carrying a spiro[fluorene-9, 9′-xanthene] (SFX) (SFX-TPAM and SFX-TPA) or spiro[fluorene-9, 9′-thioxanthene] (SFT) unit (SFT-TPAM and SFT-TPA) were synthesized through a low-cost facile route with high yields for perovskite solar cell (PSC) applications. In terms of absorption, these four compounds in the film state are all transparent at wavelengths longer than 430 nm, which is beneficial for allowing visible light to reach the perovskite active layer without being absorbed by the hole transporting layer (HTL). The photovoltaic performance of the inverted PSCs based on these small molecular HTMs with the device architecture of glass/ITO/HTL/CH3 NH3 PbI3 /C60 /BCP/Ag was tested. Only SFX-TPAM had its highest occupied molecular orbital (HOMO) level matched with the valence band of CH3 NH3 PbI3 . The inverted PSC based on a dopant-free SFX-TPAM HTL achieves a power conversion efficiency of 10.23% under the illumination of standard one sun lighting, which is better than that (8.17%) of the cell based on dopant-free spiro-OMeTAD. The better photovoltaic performance of SFX-TPAM compared to spiro-OMeTAD may be due to the MAPbI3 film deposited on it having better quality. These results indicate that the facilely synthesized, low-cost SFX based small molecules can be used as the HTMs for PSCs.